Lead‐Glazed Rustiques Figulines (Rustic Ceramics) of Bernard Palissy (1510–90) and his Followers. (17th June 2016) - Bouquillon, A.; Castaing, J.; Barbe, F.; Paine, S.R.; Christman, B.; Crépin‐Leblond, T.; Heuer, A.H.
Abstract : The glaze chemistry of a group of rustiques figulines attributed to the renowned French potter Bernard Palissy (1510–90), or to his followers and imitators, has been determined non‐destructively using PIXE and PIGE analyses. The glazes are all lead silicates, the colourants being transition metal oxides—CuO, CoO, MnO and Fe2 O3 —with a small addition of SnO2 to some of the glazes being common. Some distinction can be made between the various fabricated objects based on details of the overall composition and on the concentrations of the various colourants. The presence of B2 O3 in any glaze, even in quantities as small as 0.1–0.3%, indicates a post‐16th century production. Additionally, B2 O3 in larger quantities, a few per cent or greater, very probably indicates an 18th–19th century production. However, at least one object known to be of 19th century production contains no B2 O3 .